Optimizing Surgical Outcomes for Skull Base Epidermoid Cysts - Waqar, Mueez; Shoakazemi, Alireza; Barber, James; Pathmanaban, Omar N.; Rutherford, Scott A.; King, Andrew T.; Hammerbeck-Ward, Charlotte (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction Surgery for skull base epidermoid cysts (SBECs) has several inherent risks including aseptic meningitis and cerebrospinal fluid (CSF) malabsorption. Perioperative measures to reduce the likelihood of such complications have not been evaluated, and this study sought to compare outcomes before and after implementation of an institutional perioperative protocol in the management of SBECs.Methods Review of a prospective database of surgically managed SBECs. Outcomes were compared before (2003–2008) and after (2010–2021) implementation of a perioperative protocol including intraoperative hyper-irrigation, prolonged course of postoperative steroids, and aggressive management of CSF malabsorption.Results A total of 39 patients were included: 12 before and 27 after implementation of the protocol. The groups were similar with respect to mean age (p = 0.99), gender (p = 0.29), surgical approach—most commonly retrosigmoid (p > 0.99)—and extent of resection—most commonly total or near total (p = 0.64). The post-protocol implementation group had a significantly lower rate of CSF diversion (p = 0.04). The overall rates of hydrocephalus (7 vs. 30%), CSF leak (19 vs. 33%), bacterial meningitis (15 vs. 33%), and mean length of stay (12 vs. 49 days) were lower in the post-implementation group, although differences did not reach statistical significance. Rates of aseptic meningitis and cranial nerve palsies were similar.Conclusion Our additional perioperative measures resulted in more favorable CSF dynamics with reduced need for CSF diversion and secondary consequences such as wound leaks and infective meningitis.
Keywords: epidermoid cysts; steroids; dexamethasone; irrigation; posterior fossa